.76(.0200-x)=x
.0152-.76x=x
+.76x +.76x (x add to .76x = 1.76x)
.0152=1.76x
(divide by 1.76 to solve for x)
Working on a problem and can't figure out how the book rearranged this problem to get the following:
0.76= x/0.0200-x
then, the book rearranged to solve for x...
x= 0.0200 X 0.76/ 1.76
I don't understand how 1.76 was obtained? I see that you cross multiply to get 0.0200 X 0.76, but can't figure out how 1.76 was obtained...
3 answers
Thank you, but i'm still a little confused. I understand everything until the +.76x + .76x (x add to .76x=1.76x) Are you saying to add .76x + .76x then, take the sum of that and add to .0152? I still can't get the 1.76...
x+ .76x =1.76x
Or
1x+.76x=1.76x
Or
1x+.76x=1.76x